Upaya Kolaboratif Pemberdayaan Sumberdaya Manusia dalam Percepatan Penanggulangan Covid-19 Melalui Strategi Penguatan Ketahanan Pangan Wilayah - Nurul Isnaini; Hani Ristiawan; Bebri Gayananda Ria Dewi; Siski Andini Sukowati; Didik Prasetyo; Akifa Laila Rusyda; Purnawati Hustina Rachman (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
The Covid-19 pandemic has a major impact on the economic sector, including in Kalibeber, Mojotengah, Wonosobo Villages. It needs community empowerment efforts that touch the independence of the family scale so that each family is able to rise up and adapt to new habits during the pandemic. The program is carried out in a series of KKN-T IPB 2020, consisting of the Optimasi Pekarangan Sehat (OMAS) and Sosialisasi dan Edukasi Jamu Aplikatif (SEJATI). OMAS is assisting the development of spinach and water spinach agricultural commodities utilizing the yard of the house. Activities carried out include seeding, distributing seeds, distributing video instructions for seeding and making liquid organic fertilizer, as well as assistance through the Whatsapp group. The activity was attended by 24 members of the PKK RW 06, Kalibeber Village. The monitor at the end showed the accumulation of fertile plants of 79.2% of the total plants, the rest withered and died. As many as 75% of the plants are well cared for, meaning that they have enough water and sunlight. From the 24 participants, only 12.5% made and nourished plants using liquid organic fertilizers. SEJATI activities provide education about common compounds in herbal plants that are beneficial for the body's immunity through video media. Changes in the level of knowledge were assessed by pre-test and post-test. The target respondents were 23 people, but only 65% of the target filled out the questionnaire. The increase in the knowledge level of the respondents was 7.22%. The level of public awareness in complying with the Covid-19 protocol shows that 95.83% of respondents think it is "very important" and 4.17% say "important". Keywords: Covid-19, Wonosobo, yard, herb